Comparison of a Drug‐Free Early Programmed Dismantling PDLLA Bioresorbable Scaffold and a Metallic Stent in a Porcine Coronary Artery Model at 3‐Year Follow‐Up. Issue 6 (June 2017) - Yahagi, Kazuyuki; Yang, Yi; Torii, Sho; Mensah, Johanne; White, Roseann M.; Mathieu, Marion; Pacheco, Erica; Nakano, Masataka; Barakat, Abdul; Sharkawi, Tahmer; Vert, Michel; Joner, Michael; et al.
Abstract : Background: Arterial Remodeling Technologies bioresorbable scaffold (ART‐BRS), composed ofl ‐ andd ‐lactyl units without drug, has shown its safety in a porcine coronary model at 6 months. However, long‐term performance remains unknown. The aim of this study was to evaluate the ART‐BRS compared to a bare metal stent (BMS) in a healthy porcine coronary model for up to 3 years. Methods and Results: Eighty‐two ART‐BRS and 66 BMS were implanted in 64 Yucatan swine, and animals were euthanatized at intervals of 1, 3, 6, 9, 12, 18, 24, and 36 months to determine the vascular response using quantitative coronary angiography, optical coherence tomography, light and scanning electron microscopy, and molecular weight analysis. Lumen enlargement was observed in ART‐BRS as early as 3 months, which progressively increased up to 18 months, whereas BMS showed no significant difference over time. Percentage area stenosis by optical coherence tomography was greater in ART‐BRS than in BMS at 1 and 3 months, but this relationship reversed beyond 3 months. Inflammation peaked at 6 months and thereafter continued to decrease up to 36 months. Complete re‐endothelialization was observed at 1 month following implantation in both ART‐BRS and BMS. Scaffold dismantling started at 3 months, which allowed early vessel enlargement, and bioresorption was complete by 24 months. Conclusions: ART‐BRS has the unique quality of early programmed dismantling accompanied by vessel lumen enlargement with mild to moderate inflammation. The main distinguishing feature of the ART‐BRS from other scaffolds made from poly‐l ‐lactic acid may result in early and long‐term vascular restoration.